(untitled) (Update Dental College Journal, 2020)
A mesiodens is a most common supernumerary tooth which is one of the most significant dental anomalies at the primary and early mixed dentition stages. The reported prevalence of mesiodens in general population ranges between 0.15% to 1.9% and more frequently found in the permanent dentition but rarely found in primary dentition. Mesiodens are primarily responsible for eruption disturbances or delay of the maxillary anterior permanent teeth emergence. Therefore the dentists and parents are great concern about malocclusion and esthetic problems which is caused by mesiodense. Early detection, diagnosis and treatment of mesiodens is important to prevent further complications in permanent dentition. A case of mesiodens of 8 years old child in upper anterior region in mixed dentition and their management have been discussed. Update Dent. Coll. j: 2020; 10 (2): 26-28